Keragaman Parasitoid Ulat Penggulung Daun Pisang (Erionota thrax L) di Desa Sungai Kupah Kecamatan Sungai Kakap Kabupaten Kubu Raya - wijaya, ridho fatra (Jurnal Sains Pertanian Equator, 2014)
BIODIVERSITY OF BANANA LEAF ROLLERS CATERPILLARS (Erionota thrax) IN SUNGAI KUPAH VILLAGE SUB DISTRIC SUNGAI KAKAP OF KUBU RAYA DISTRICT RidhoFatraWijaya(1), Indri Hendarti dan TrisHarisRamadhan(2), (1)Student and (2)Lectures Agronomic Study of Agriculture Faculty Tanjungpura University ABSTRAC Parasitoids as the natural enemies of banana leaf rollers caterpillars (E. thrax) are important for biological control. Banana leaf rollers, caused crop damage which affect to production. This research aims to determine parasitoids of E. thrax in Sui.Kupah Kubu Raya District. The research was conducted in the Pest Laboratory Agriculture Faculty Tanjungpura University. The study was conducted by survey method with purposive sampling approach. E. thrax larvae and pupae were collected from Banana Leaf and the Larvae kept in a plastic jar. Feed until the parasitoid came out. The results obtained 3 types of parasitoids that attack E. thrax, called parasitoid larvae: Charops sp. and parasitoid pupae: Brachemyria sp. and Xhantopimpla sp. Parasitism percentage of E. thrax based on location are the first location in larvae 5.12% and pupa 6.45%, the second location ??in larvae 11.32% and pupa 6.89%, and the third location in larvae 5.26% and pupa 24%. Diversity index of Parasitoid species in Banana Leaf Rollers Pest is low in this garden. Dominance from three garden area is parasitoid of Brachemyria sp. is the dominant spesies on three type of plantations. Keywords: Diversity, Erionota thrax, Parasitoids.